(untitled) (Fiep Bulletin - online, 2014)
By using water it is possible to use the physical and physiological effects to treat neurological patients that represent motorical difficulties. The aquatic activities promote flexibility, strength, balance, resist, coordination and also bring cardiorespiratory benefits. Hydrocapoeira is the introduction of Capoeira in water that comes along with the objective to surpass the resistance of the water. The objective of this study is to examine the influence of Hidrocapoeira on the balance and quality of life of neurological patients. Participants were one therapeutic group, the six neurological patients (1 encephalopaty , 3 head injury , 1 stroke , 1 distonia ). The study took place at the Policlinica of the Centro Universitário Adventista de São Paulo (UNASP) during a period of four months, twice a week with each a fourtyfive minutes therapy session. To calculate the parameters it was being used a questionary of quality of life (SF-36) followed by a balance test (Scale de Berg). After four months of therapy results showed statistically significant improvement in quality of life and balance. The group of patients showed is 45,87% improvement in the fallindex of the balance test. The assessment of quality of life 25,87% is functional capacity; 27,27% is physical aspects; 66,75% is emotional aspects; 19,00% general state of health, 53,85% is vitality; 58,73% is social aspects; 18,45% is mental Health and 21,40 is pain, on the patient group. It may be concluded that the simultaneous movements of Hydrocapoeira provide benefit for these neurological patients, both in balance and quality of life.